Development and Evaluation of Foundational Cancer Science Graduate Courses in the Evolving Landscape of Cancer Research - Eugene Kandel; Michael Nemeth; Richard O’Connor; Stephanie Tzetzo; AnneMarie W. Block; Spencer Rosario; Tatiana Shaurova; Mukund Seshadri; Pamela A. Hershberger (Journal of Cancer Education, 2026)
Roswell Park is a free-standing Comprehensive Cancer Center in Buffalo, New York and serves as the academic home to a doctoral program in Cancer Sciences. To meet the evolving cancer research landscape, we developed and implemented a series of sequential Integrated Cancer Sciences (ICS-I, ICS-II, and ICS-III) courses that provide a strong, multi-disciplinary foundational knowledge to graduate trainees, regardless of their eventual specialization. These courses span the entire spectrum of cancer research from basic biology to population science/epidemiology, cancer therapeutics, and clinical oncology and were intentionally developed to prepare trainees for diverse careers in cancer research. The engagement and participation of basic, population science, and clinical faculty was integral for successful implementation of these courses. Survey responses were collected from students who had completed the ICS courses since 2018 to evaluate course content, depth, and perceived value. Ninety-five percent of respondents felt the depth of course content was appropriate for graduate study. A majority of trainees (74%) felt that the ICS courses significantly expanded their knowledge base beyond their immediate interest area. We continue to assess and update the content of ICS courses to better reflect the growing training needs, especially in emerging technologies such as artificial intelligence (AI).

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Effects of mycobacterium cell wall fraction on embryo development following in vitro embryo production and pregnancy rates following embryo transfer in virgin dairy heifers - W. Brown; M. Oliveira; R. Reis Silva; K. Woodruff; B. Bisha; D. Demetrio; J. Block (Theriogenology, 2024)

Assignment of tracks from tagged Atlantic bluefin tuna Thunnus thynnus to potential stocks using behavioural differences and habitat partitioning - Simon Dedman; Emilius A. Aalto; Michael J. W. Stokesbury; Robert J. Schallert; Michael R. Castleton; Barbara A. Block (Frontiers in Marine Science, 2023)
Introduction Atlantic bluefin tuna (ABT) are large, migratory pelagic predators of high economic importance. ABT are currently managed as two independent stocks assigned to discrete spawning areas (Gulf of Mexico, and Mediterranean); however, stock overlap outside spawning areas makes accurate assignment of catch to stock-of-origin difficult. Methods Within this two-stock paradigm, we characterised stock-specific spatial distributions and behaviours by comparing habitat usage and vertical movement behaviours of 118 electronically tagged adult ABT spatially assigned to the GOM and Med spawning grounds. These spatial and behavioural differences were used in tests to probabilistically assign unknown individuals (which did not visit the GOM/Med spawning areas) to a stock. Results This new methodological approach using existing tag data, enables increased assignment of a track to a potential stock, to be achieved before genetic assignments. We identified certain markedly different movement patterns, range extents, depth use preferences (and associated area usage), migration directness and speeds, corresponding distance from shore, and mesopelagic-layer visitation. The probabilistic assignment approach had 97% in-bag testing accuracy, then assigned 190 individuals to a stock, doubling the number of assigned stock-of-origin tracks in our dataset, and potentially revealing novel movement and behaviour patterns among pre-spawning-age ABT. Discussion This approach can be easily adapted to other study species, more stocks, and different testing variables, hopefully serving as a useful addition to the fisheries management toolkit.

Informing Management of Atlantic Bluefin Tuna Using Telemetry Data - Rebecca Whitlock; Robert J. Schallert; Michael J. W. Stokesbury; Michael Castleton; Barbara A. Block (Frontiers in Marine Science, 2022)
Sustainable management of exploited marine fish and wildlife populations requires knowledge about their productivity. Survival from natural causes of mortality is a key component of population productivity, but is notoriously difficult to estimate. We evaluate the potential for acoustic telemetry as a long-term monitoring tool to estimate rates of natural mortality. We present a Bayesian multistate mark-recapture model for telemetry data collected over a decade from 188 Atlantic bluefin tuna ( Thunnus thynnus) and apply it to estimate the rate of natural mortality using only acoustic tag detections for all animals, or using acoustic tag detections for 96 single-tagged tuna plus acoustic tag detections combined with estimated positions from pop-up satellite archival tags for 92 double-tagged animals. We support the model for bluefin tuna with a simulation study to quantify bias in estimates of population dynamics parameters and investigate the effect of auxiliary information from satellite tagging on mortality rate estimates for different acoustic tag detection probability scenarios. We obtained posterior estimates of the instantaneous annual natural mortality (survival) rate across a decade of tagging for Atlantic bluefin tuna of 0.17 yr -1 (0.84 yr -1 ) both using only acoustic tagging data, and using a combination of acoustic and satellite tagging data. Use of a prior implying a higher rate of fishing mortality yielded an instantaneous annual natural mortality (survival) estimate of 0.10 yr -1 (0.90 yr -1 ), with combined acoustic and satellite tag data. Results from the simulation study indicate that the use of satellite tags can improve the precision and accuracy of estimates of detection probabilities, area-specific movement probabilities and mortality rates, where the extent of the improvement depends on true underlying acoustic tag detection probabilities. Our work demonstrates that long-term acoustic tagging data sets have strong potential for monitoring of highly migratory marine fish and wildlife populations, providing information on a number of key parameters, including survival and movement rates. However, improved information on tag reporting rates or fishing mortality is needed to better separate natural and fisheries mortality for Atlantic bluefin tuna.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Do elevated blood levels of omega-3 fatty acids modify effects of particulate air pollutants on fibrinogen? - Daniel Croft; Robert Block; Scott J. Cameron; Kristin Evans; Charles J. Lowenstein; Frederick Ling; Wojciech Zareba; Philip K. Hopke; Mark J. Utell; Sally W. Thurston; Kelly Thevenet-Morrison; David Q. Rich (Air Quality, Atmosphere & Health, 2018)

Fungal and herbivore elicitation of the novel maize sesquiterpenoid, zealexin A4, is attenuated by elevated CO2 - Shawn A. Christensen; Alisa Huffaker; James Sims; Charles T. Hunter; Anna Block; Martha M. Vaughan; Denis Willett; Maritza Romero; J. Erik Mylroie; W. Paul Williams; Eric A. Schmelz (Planta, 2018)

Maternal prenatal intake of one-carbon metabolism nutrients and risk of childhood leukemia - Amanda W. Singer; Steve Selvin; Gladys Block; Carla Golden; Suzan L. Carmichael; Catherine Metayer (Cancer Causes & Control, 2016)

Direct evidence that HSV DNA damaged by ultraviolet (UV) irradiation can be repaired in a cell type-dependent manner - Scott Millhouse; Xiaohe Wang; Nigel W. Fraser; Lisa Faber; Timothy M. Block (Journal of NeuroVirology, 2012)

Linear and angular control of circular walking in healthy older adults and subjects with cerebellar ataxia - Adam D. Goodworth; Caroline Paquette; Geoffrey Melvill Jones; Edward W. Block; William A. Fletcher; Bin Hu; Fay B. Horak (Experimental Brain Research, 2012)

Passive Transdermal Systems Whitepaper Incorporating Current Chemistry, Manufacturing and Controls (CMC) Development Principles - Glenn A. Van Buskirk; Daniel Arsulowicz; Prabir Basu; Lawrence Block; Bing Cai; Gary W. Cleary; Tapash Ghosh; Mario A. González; David Kanios; Margareth Marques; Patrick K. Noonan; Terrance Ocheltree; et al. (AAPS PharmSciTech, 2012)

Evidence that herpes simplex virus DNA derived from quiescently infected cells in vitro , and latently infected cells in vivo , is physically damaged - Scott Millhouse; Ying-Hsiu Su; Xianchao Zhang; Xiaohe Wang; Benjamin P Song; Li Zhu; Emily Oppenheim; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2010)

Habitat and behaviour of yellowfin tuna Thunnus albacares in the Gulf of Mexico determined using pop‐up satellite archival tags - K. C. Weng; M. J. W. Stokesbury; A. M. Boustany; A. C. Seitz; S. L. H. Teo; S. K. Miller; B. A. Block (Journal of Fish Biology, 2009)
This study presents the first data on movement, habitat use and behaviour for yellowfin tuna Thunnus albacares in the Atlantic Basin. Six individuals were tracked in the Gulf of Mexico using pop‐up satellite archival tags. Records up to 80 days in length were obtained, providing information on depth and temperature preferences as well as horizontal movements. Thunnus albacares in the Gulf of Mexico showed a strong preference for the mixed layer and thermocline, consistent with findings for this species in other ocean basins. Fish showed a diel pattern in depth distribution, remaining in surface and mixed layer waters at night and diving to deeper waters during the day. The vertical extent of T. albacares habitat appeared to be temperature limited, with fish generally avoiding waters that were >6° C cooler than surface waters. The vertical and thermal habitat usage of T. albacares differs from that of bigeye Thunnus obesus and bluefin Thunnus thynnus , Thunnus orientalis and Thunnus maccoyii tunas. These results are consistent with the results of earlier studies conducted on T. albacares in other oceans.

Movements, behavior, and habitat utilization of yellowfin tuna (Thunnus albacares) in the northeastern Pacific Ocean, ascertained through archival tag data - Kurt M. Schaefer; Daniel W. Fuller; Barbara A. Block (Marine Biology, 2007)

Results of satellite tagging of Atlantic bluefin tuna, Thunnus thynnus, off the coast of Ireland - Michael J. W. Stokesbury; Ronan Cosgrove; Andre Boustany; Daragh Browne; Steven L. H. Teo; Ronald K. O’Dor; Barbara A. Block (Hydrobiologia, 2007)

High apex predator biomass on remote Pacific islands - Charlotte Stevenson; Laure S. Katz; Fiorenza Micheli; Barbara Block; Kimberly W. Heiman; Chris Perle; Kevin Weng; Robert Dunbar; Jan Witting (Coral Reefs, 2007)

Annual migrations, diving behavior, and thermal biology of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre Boustany; Heidi Dewar; Michael J. W. Stokesbury; Kevin C. Weng; Shana Beemer; Andrew C. Seitz; Charles J. Farwell; Eric D. Prince; Barbara A. Block (Marine Biology, 2007)

Herpes simplex virus type 1 ICP4 deletion mutant virus d120 infection failed to induce apoptosis in nerve growth factor–differentiated PC12 cells - Benjamas Aiamkitsumrit; Xianchao Zhang; Timothy M Block; Pamela Norton; Nigel W Fraser; Ying-Hsiu Su (Journal of NeuroVirology, 2007)

The stability of herpes simplex virus type I genomes in infected Vero cells undergoing viral induced apoptosis - Ying-Hsiu Su; Xianchao Zhang; Benjamas Aiamkitsumrit; Qiyi Tang; Gerd Maul; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2006)

Vestibular–Podokinetic interaction without vestibular perception - G. Melvill Jones; W. A. Fletcher; K. D. Weber; E. W. Block (Experimental Brain Research, 2005)

Movement and environmental preferences of Greenland sharks (Somniosus microcephalus) electronically tagged in the St. Lawrence Estuary, Canada - Michael J. W. Stokesbury; Chris Harvey-Clark; Jeffrey Gallant; Barbara A. Block; Ransom A. Myers (Marine Biology, 2005)

Mechanized land preparation in forest-based fallow systems: The experience from Eastern Amazonia - M. Denich; K. Vielhauer; M.S. de A. Kato; A. Block; O.R. Kato; T.D. de Abreu Sá; W. Lücke; P.L.G. Vlek (Agroforestry Systems, 2004)

Podokinetic after-rotation in patients with compensated unilateral vestibular ablation - Weber K.; Fletcher W.; G. Melvill Jones; Block E. (Experimental Brain Research, 2002)

Does the cerebellum play a role in podokinetic adaptation? - Gammon M. Earhart; William A. Fletcher; Fay B. Horak; Edward W. Block; Kimberly D. Weber; Oksana Suchowersky; Geoffrey Melvill Jones (Experimental Brain Research, 2002)

Planetary habitability: is Earth commonplace in the Milky Way? - S. Franck; A. Block; W. Bloh; C. Bounama; I. Garrido; H.-J. Schellnhuber (The Science of Nature, 2001)

Seasonal and long-term variation in body-water content of an Antarctic springtail - a response to climate change? - Block W.; Convey P. (Polar Biology, 2001)

Adaptive Management on Public Lands in the United States: Commitment or Rhetoric? - W. H. MOIR; W. M. BLOCK (Environmental Management, 2001)

Thermal tolerance and acclimation response of larvae of the sub-Antarctic beetle Hydromedion sparsutum (Coleoptera: Perimylopidae) - J. S. Bale; W. Block; M. R. Worland (Polar Biology, 2000)

Forestry Education: Adapting to the Changing Demands on Professionals - V. Alaric Sample; Paul C. Ringgold; Nadine E. Block; James W. Giltmier (Journal of Forestry, 1999)
Recent evolution in the practice of forestry can be linked to changes in the public's perception of sustainability and to developments in science, communications, and global markets. In response, when hiring graduates of professional forestry programs, forestry employers have changed the set of skills and competencies sought. A nationwide survey of forestry employers, educators, and recent graduates, conducted to assess how well US forestry programs are preparing professionals to practice forestry today, reveals some discrepancies between what employers want and what the schools provide. External financial and political pressures on higher education make it difficult for educators to close these gaps, but opportunities exist for employers to help.

Collembola of sub-Antarctic South Georgia - P. Convey; P. Greenslade; R. J. Arnold; W. Block (Polar Biology, 1999)

Population Responses of Peromyscus Resident in Iowa Cornfields Treated with the Organophosphorus Pesticide COUNTER® - Elizabeth K. Block; Thomas E. Lacher; Larry W. Brewer; George P. Cobb; Ronald J. Kendall (Ecotoxicology, 1999)

Spatial dynamics of two introduced species of carabid beetles on the sub-Antarctic island of South Georgia - G. J. Brandjes; W. Block; G. Ernsting (Polar Biology, 1999)

Horizontal movements and depth distribution of large adult yellowfin tuna ( Thunnus albacares ) near the Hawaiian Islands, recorded using ultrasonic telemetry: implications for the physiological ecology of pelagic fishes - R. W. Brill; B. A. Block; C. H. Boggs; K. A. Bigelow; E. V. Freund; D. J. Marcinek (Marine Biology, 1999)

Hydrology, water availability and tundra ecosystem function in a changing climate: the need for a closer integration of ideas? - I. D. Hodkinson; N. R. Webb; J. S. Bale; W. Block (Global Change Biology, 1999)
Hydrologists and ecologists studying tundra ecosystems have worked largely independently, with little cross‐fertilization between disciplines. Their disciplines are, however, inextricably linked by a need to understand the dynamics and significance of the common substance water, in its liquid, solid and gaseous state within tundra environments. The impacts of predicted long‐term changes in climate have particularly important consequences for the functioning of tundra systems and there is a pressing need to initiate studies that integrate hydrological and ecological methodologies and concepts. Our paper attempts to summarize existing information on the role of water within tundra ecosystems, to emphasize the fundamental links between the biotic and the physico/chemical environments and to suggest how a closer integration of ideas might be achieved. Given the breadth of the subject matter the paper is intended to be illustrative rather than comprehensive. The paper examines the physical impacts of water in its various states on the tundra environment, emphasizing in particular the causes of spatial variation in water availability to living organisms. The significance of water is discussed for a range of organism groups, including plants, invertebrates and microorganisms and its pivotal role in ecosystem function and disturbance stressed. The need to develop integrated hydological/ecological models for tundra systems on different spatial scales is emphasized.

Motor learning in the "podokinetic" system and its role in spatial orientation during locomotion - K. D. Weber; W. A. Fletcher; C. R. Gordon; G. Melvill Jones; E. W. Block (Experimental Brain Research, 1998)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Comparative nutritional ecology of grass-feeding in a sub-Antarctic beetle: the impact of introduced species on Hydromedion sparsutum from South Georgia - S. L. Chown; W. Block (Oecologia, 1997)